Small-sized diode thermal sensor - Політанський, Леонід Францович; Яганов, Петро Олексійович; Лесінський, Валентин Вікторович (Eastern-European Journal of Enterprise Technologies, 2012)
The design implementation of the small unpacked silicon diode thermal sensor, manufactured by the microelectronic technology at the silicon structures with the dielectric isolation is the most accurate and reproducible technology for the measurement of temperature in the range 4 - 500 K. The die form of the micro thermal sensor minimizes the sizes and weight, and reduces its thermal resistance and lag; and the insulating cover protects the device from the external influence. The manufacture of the die form of the microelectronic sensor consists of 3 phases: a crystal cut into workpieces and provision of the external connections by the thermocompression of conductors; the micro sensors assembly; testing and control measurements for selection of the micro sensors according to the defined criteria. The results showed that the thermal resistance of the sensor on silicon structures with the dielectric isolation of the volume not more than 1 мм3 in the die form on a flexible crystal holder would not exceed 20 K / W. The suggested design of the thermal sensor could be applied in medicine, food industry and methods of technological processes control, etc